The Influence of Using Social Media in the 5.0 Society Era on Strengthening the Tolerant Character of Class XI Students at SMA Negeri 2 Kutacane T.P 2022/2023 - Safira, Aulia; Lahmuddin, Lahmuddin (Holistic Science, 2023)
This study aims to determine the Effect of Social Media Use in the Era of 5.0 Society on Strengthening the Character of Tolerance of Class XI Students at SMA Negeri 2 Kutacane T.P 2022/2023. This study used quantitative research. The object of this study was grade XI students of SMA Negeri 2 Kutacane and data collection techniques using questionnaires, observation and documentation. The data analysis techniques used are validity tests, reliability tests, normality tests and using hypothesis tests through simple regression. Based on the calculation of the validity test there are 20 questions, after conducting the validity test >3.88 then it is declared entirely valid, the reliability test value (x) obtained is 0.696 and the value (y) obtained is 0.703 then it is declared reliable, the normality test value obtained is 0.200 then it is normally distributed. And after a simple linear regression hypothesis test, namely t count greater than t table at a significance level of 5%, namely 3.653 > 1.710 with a total of 26 respondents, which means that there is an influence of social media use in the era of 5.0 society on strengthening the tolerance character of grade XI students of SMA Negeri 2 Kutacane T.P 2022/2023, and a simple linear regression equation Y = 38 was obtained, 406 + 0.507 X, which means that if X is increased by one unit then Y will increase by 0.507. This shows that the more the use of social media, the higher the tolerance character of students. The R Square (R²) value of 0.357 means that the use of social media has an effect of 35.7% on the tolerance character of students at SMA Negeri 2 Kutacane